Civil Liability Against Business Actors Committing Violations of Halal Labeling Based on Law no. 8 of 1999 Concerning Consumer Protection - Emir Syarif Fatahillah Pakpahan; Dewantara Dewantara; Bella Yuli Savira; Budi Valendra (IHSA Institute, 2021)
The plurality of products traded in the market are suspected of not having halal certificates. This condition is very concerning, especially for Indonesian Muslims. Indonesia's market share is flooded with not only domestic products, but also imported products, as an implication of the implementation of AFTA (ASEAN Free Trade Area) and MEA (Asean Economic Community). For Muslims, the halalness of a product is very urgent. The inclusion of halal food labels is a form of protection to consumers that halal products are consumed. Law Number 8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK) regulates civil sanctions for business actors violating the halal label. Law Number 33 of 2014 concerning Guaranteed Halal Products (hereinafter referred to as the JPH Law) also regulates sanctions for business actors who do not maintain product halalness and do not include halal certificates on products already labeled as halal. The presence of UU JPH and PP No. 31 of 2019 is expected to bring fresh air to change the procedure and registration system for halal certification from voluntary to mandatory. This journal uses normative juridical research, namely analyzing legal products such as laws and regulations. The data used are secondary data, namely books relevant to the research. The research uses qualitative analysis, where the problem is described in the form of sentences.